High-resolution fMRI investigations of the fingertip somatotopy and variability in BA3b and BA1 of the primary somatosensory cortex. (17th December 2016) - Pfannmöller, Jörg Peter; Greiner, Marvin; Balasubramanian, Mukund; Lotze, Martin
Highlights: Differences in the functional maps of the fingertip somatotopy in BA1 and BA3b. Analysis of the functional and anatomical contribution to the variability in the somatotopy. Evaluation of left-right symmetry in the fingertip somatotopy. Group analysis of the fingertip somatotopy in BA3b and BA1. Maximization of fine-scale mapping and statistical sensitivity in group comparisons. Abstract: The fingertip somatotopy in BA1 and BA3b of monkeys exhibits characteristic differences with a more discrete separation of the body parts in BA3b and a continuous orientation column-like structure in BA1. We present evidence for similar differences in the human somatotopy using BOLD fMRI for the investigations. Though the variability between the individual maps was large, we found a group-wide somatotopic representation in BA3b and BA1. The variability due to anatomical differences was small in our sample. This was demonstrated by comparing exact shortest distances in the individual brains and after nonlinear normalization to the group space template, for the removal of the individual anatomical variability. Distance mapping along Dijkstra paths was found to be a valid approximation to exact shortest paths only in the individual brains. The degree of fine-scale detail mapping was improved if valid surface distances instead of 3D Euclidean distances were applied. A further improvement was achieved by mapping the distances between all neighboring fingertips instead of only the outer fingertips. Taking into account all optimizations we found mirror symmetry of the somatotopy with respect to the interhemispheric gap.